2009
DOI: 10.1074/jbc.m109.016907
|View full text |Cite
|
Sign up to set email alerts
|

The N Terminus of Connexin37 Contains an α-Helix That Is Required for Channel Function

Abstract: The cytoplasmic N-terminal domain of connexins has been implicated in multiple aspects of gap junction function, including connexin trafficking/assembly and channel gating. A synthetic peptide corresponding to the first 23 amino acids of human connexin37 was prepared, and circular dichroism and nuclear magnetic resonance studies showed that this N-terminal peptide was predominantly ␣-helical between glycine 5 and glutamate 16. The importance of this structure for localization of the protein at appositional mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 54 publications
5
19
0
Order By: Relevance
“…An N-terminal deletion mutant of ShakBL, an innexin protein found in Drosophila, fails to induce conductance when paired homotypically, and induces much lower conductance when paired heterotypically with functional ShakBL [43]. These are consistent with the works on Cx37 showing that the N-terminal deletion mutants are mostly non-functional [44,45]. It is possible that the conformations of all purified INX-6 Δ N channels are fixed in a closed state by this truncation, which leads to the better crystallinity.…”
Section: Discussionsupporting
confidence: 87%
“…An N-terminal deletion mutant of ShakBL, an innexin protein found in Drosophila, fails to induce conductance when paired homotypically, and induces much lower conductance when paired heterotypically with functional ShakBL [43]. These are consistent with the works on Cx37 showing that the N-terminal deletion mutants are mostly non-functional [44,45]. It is possible that the conformations of all purified INX-6 Δ N channels are fixed in a closed state by this truncation, which leads to the better crystallinity.…”
Section: Discussionsupporting
confidence: 87%
“…10 Bioinformatic secondary structure predictions and NMR studies suggest that the -group connexin NT domain possesses a predominantly -helical pore domain structure between positions W4 and S18. 30 indicate a 15% increase in  j and reduced cation selectivity associated with the Cx40 G2 mutation (Fig. 2), consistent with the interpretation of increased pore volume and less electrostatic charge in the vicinity of the amino terminus.…”
Section: Discussionsupporting
confidence: 82%
“…However, all constructs containing at least 9 amino acids formed gap junction plaques, implying that the absolute length of the NT and the identities of specific amino acids are not requirements for normal biosynthesis of gap junctions. In agreement with these findings, Kyle et al [26] found that expression of a Cx37 mutant containing prolines at positions 10 and 15 (instead of the normal Leu15 and Gln15) also formed plaques. However, all of these mutations disrupted hemichannel and channel function.…”
Section: Role Of Nt In Formation Of Functional Gap Junction Channelsmentioning
confidence: 52%
“…It is interesting that the critical residues implicated in determining these various physiological properties are among the most divergent amino acids within the NT domain (see [26, 32, 35]). Although overall the sequence of this domain is quite conserved, the substitutions confer many of the characteristic properties that differentiate channels formed of different connexins.…”
Section: Roles Of Nt Amino Acids In Channel Gating Unitary Conducmentioning
confidence: 99%
See 1 more Smart Citation